Jejak rasul 4 berjuta wajah satu akidah - Wan Alias Abdullah
This episode views travel to historic places such as Kazakhstan, China, Maldives, New Delhi and Islamabad where prominent prophets (pre and post-Islamic period) once reside, flourish and died.